The Influence of Psychological Capital and Transformational Leadership in Encouraging Innovative Behavior and Employee Performance: Testing the Readiness to Change of Microenterprise Employees in Situbondo District - Yusuf Rio Wahyu Prayogo; Riani Rachmawati (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to understand the role of psychological capital and transformational leadership in encouraging innovative behavior and employee performance, by considering readiness for change as a mediating variable. The focus of the study was directed at the Micro Business sector in Situbondo, which has so far focused more on technical and financial aspects, while the psychological aspects of employees are often ignored. In fact, this aspect contributes significantly to business competitiveness and sustainability. The research approach used was quantitative with the Structural Equation Modeling (SEM) method based on Partial Least Squares (PLS). The results showed that psychological capital had a positive and significant effect on innovative behavior and employee performance. In addition, readiness for change was proven to act as a mediating variable that strengthened the influence of psychological capital on both variables. Transformational leadership also had a positive effect on innovative behavior, but did not have a significant effect on employee performance. However, the effect of transformational leadership on innovative behavior can be significantly mediated by readiness for change. So far, human resource development in this sector tends to ignore employee psychological strengths such as optimism, self-efficacy, hope, and resilience, even though these elements have proven crucial in creating an innovative and high-performing workforce. Practical advice from this study is the need for interventions specifically designed by the government or policy makers in the form of positive psychology-based training.